A History of the American Association of Pathologists' Assistants: Creating an Organization, Winning Hearts and Minds, and Building an Invaluable Profession - Thomas L. Reilly BHS, PA (ASCP); James R. Wright MD, PhD (Elsevier, 2020)
Thomas D. Kinney and Duke University started the first formal university-based training program for pathologists' assistants in 1969. Over the next 2 years, 2 more university-based programs were established. All 3 programs were affiliated with nearby Veterans Administration Hospitals and were funded as a pilot study by the US Veterans Administration to address a looming shortage of pathologists. Early graduates of these programs discovered that the concept of pathologists' assistants with well-defined skill sets encompassing both surgical and autopsy pathology was not initially accepted by important elements of organized pathology. Indeed, many academic pathologists were opposed to the concept from the outset. In the face of such opposition, a group of practicing pathologists' assistants created and incorporated their own professional organization, the American Association of Pathologists' Assistants, to provide support, advocacy, and continuing education for individual practicing pathologists' assistants. The history of the American Association of Pathologists' Assistants and its role in the establishment and success of the pathologists' assistant profession are described utilizing personal communications as well as published historical sources.